Investigation of Wear Properties of Al-SiC Composite Materials Produced by Powder Metallurgy Method - Halil ARIK (Gazi Üniversitesi Fen Bilimleri Dergisi, 2019)
Aluminum matrix and ceramic particle reinforced composites are preferred materials especially in aerospace and aviation field due to their high abrasion and thermal expansion resistance compared to matrix material. In this study, SiC reinforced composite material was produced by applying powder metallurgy production technique as solid state method. Initially, to obtain composite powder, mechanically grinding and mixing process of the aluminum and SiC powder was realized in turbula device containing steel ball. Then, mechanical tests and metallographic examinations of powder metal composite samples which were pressed at 500 MPa pressure and sintered for 2 hours at 650 °C were performed. The aim of this study, by obtaining the homogeneous distribution of the SiC strengthening particles in the aluminum matrix structure was to improve the mechanical properties of the matrix structure, particularly the abrasive wear resistance. Tests results have shown that the composite has better wear resistance than aluminum powder metal part. It has been observed that by adding silicon carbide into the aluminum, abrasive wear resistance and other mechanical properties considerably improved.